DETERMINANTS OF FINANCIAL WELLNESS OF RURAL HOUSEHOLDS IN THE HILL DISTRICTS OF UTTARAKHAND: AN EMPIRICAL APPROACH - Purohit, Ajay; Chopra, Gaurav; Dangwal, Parshuram G (Indian Journal of Finance and Banking, 2022)
The study examines significant contributors to financial wellness for rural households in the hill districts of Uttarakhand. The study takes a sample of 666 respondents through multi-stage stratified random sampling from Self-Help Groups (SHGs) and Cooperatives members, and all are small and marginal farmers. A field survey was conducted using a structured questionnaire. Except for financial knowledge and numeracy, all other constructs, such as cash management, savings behavior, risk-credit management, financial attitudes, and financial wellness, were measured on a seven-point Likert scale ranging from strongly disagree to strongly agree. Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modelling (SEM) were conducted on 628 valid samples using SPSS 23 and AMOS 23. The results from the analysis revealed that cash management, savings behavior, and financial attitudes significantly contribute to financial wellness. The study found that households have the reasonable financial knowledge and financial numeracy skills. The study also found that savings behavior has a mediating effect on the relationship between cash management and financial wellness. The study is useful for rural development stakeholders and policymakers to strategically focus on financial inclusion programs. JEL Classification Codes: D14, G51, G52, G53, I30.